Leadership, psychological contract and empowerment: their relationships in Mexican border organizations - Vargas Salgado, María Marisela; Máynez Guaderrama, Aurora Irma (Acta Universitaria, 2019)
Nowadays, companies consider essential to develop the skills of their leaders, in order to achieve organizational success. In this research, the objective was to inquire the influence that transformational leadership has on the psychological contract and its influence on empowerment. The investigation was developed in the context of the northern border of Chihuahua through a quantitative , not experimental, transversal, descriptive, and causal study. In total, 310 employees who work as middle and senior managers in the auto-parts sector of the export manufacturing industry were surveyed; they were selected for convenience. The data were analyzed using the Structural Modeling statistical technique based on partial least squares (PLS). The results reveal that the relationship of transformational leadership significantly impacts directly and indirectly on empowerment, through the mediation of the psychological contract.